Optimizing the Financial Management Behavior of Msme Actors Through Digital Financial Knowledge in the Digital Era - Muhammad Taufan Ashshiddiqi; Taufiq Rahmat (UIN Sunan Gunung Djati Bandung, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are not foreign because when the economic crisis hit the Indonesian nation, MSMEs were able to survive the turmoil of the crisis. It has been proven that the MSME sector can stand up and survive in the face of an economic crisis. However, not all MSMEs can manage finances, even though this habit of managing finances is critical. This research aims to determine, analyze and provide recommendations regarding Digital Financial Knowledge and Financial Management Behavior in MSMEs in Bandung City. The research method uses an explanatory method with a quantitative approach. They are collecting data using a questionnaire instrument selected by the researcher with a simple random sampling technique. Then the data were analyzed using descriptive analysis and structural equations Structural Equation Modeling (SEM) with the help of Smart-PLS. Conclusion: The findings show that the relationship between financial behavior management variables and digital financial knowledge is unidirectional and significantly positive so that the description equation model is obtained, namely, the higher the level of financial management behavior of MSME actors, the more digital financial knowledge tends to increase. MSME knowledge about digital financial risks, digital financial risk control knowledge, and understanding of how to secure personal information still needs to be improved to align with the smart city vision of the Bandung City Government. Other factors that affect digital financial knowledge have not been studied, and these factors become recommendations for further research.